Welcome to the June 2024 Issue (Vol: 30, No: 3) and Current News of the European Journal of Therapeutics - Balat, Ayşe; Eren, Şevki Hakan; Menzilcioğlu, Mehmet Sait; Bahşi, İlhan; Doğan, İlkay; Kaplan, Davut Sinan; Karadağ, Mehmet; Özçelik, Ayşe Aysima; Sarı, Fatih; Yıldız, Hamit; Akbaba, Murat; Başkonuş, İlyas (European Journal of Therapeutics, 2024)
Dear Colleagues, It is our pleasure to share the valuable articles in a new issue of the Eur J Ther (2024; Vol: 30, Issue: 3). We would like to take this opportunity to thank once again the authors who submitted valuable papers to the journal and the referees who evaluated these articles. In April 2023, we shared that the editorial team of Eur J Ther underwent many changes and was updated with a dynamic team [1]. We then made a series of improvements in a short period of time. First, we strengthened our editorial team with many internationally respected academics [2]. In July 2023, Web of Science calculated the journal’s impact factor value for the first time as 0.3 [3]. Then, with the dedicated work of the updated editorial team, the journal was soon included in many essential indexes such as Index Copernicus (approved 2023-10-31), ERIH PLUS (approved 2023-06-21), BASE (approved 2023-11-30), and Sherpa Romeo (approved 2023-09-27). As a result of our application, as of the beginning of 2024, articles that have not yet been assigned to the issue and are in early view have started to be indexed in the Web of Science in a short time [4]. This is reflected in the Times Cited and Publications Over Time graphic on the Web of Science (Fig. 1) [5]. Another significant development was that from 2024 onwards, the journal will be published six issues a year instead of four. Through this editorial, we would like to share other good recent news and the journal metrics recently published by Clarivate Analytics with you, our valuable followers [6]. According to Journal Citation Reports 2024, Eur J Ther's journal impact factor value is 0.3 (Fig. 2) [6]. We believe that your valuable studies and contributions will increase this value. The most pleasing result in the Journal Citation Reports 2024 data [6] is that the Journal Impact Factor Quartile value of Eur J Ther, which is in the Medicine, General & Internal Category, was determined as Q3. The Journal Impact Factor (JIF) Quartile for the Eur J Ther has been calculated for the first time this year, and we are delighted to observe that it is the Q3. In other words, according to the Journal Impact Factor value, Eur J Ther ranks 243rd among 325 journals in the Medicine, General & Internal Category (JIF Rank 243/325). However, we know we should do our best to go one step further and reach better levels. As Stephen Hawking says, “However difficult life may seem, there is always something you can do and succeed at.” We look forward to sharing more good news with you. Yours Sincerely,